Análisis de la volatilidad del índice principal del mercado bursátil mexicano, del índice de riesgo país y de la mezcla mexicana de exportación mediante un modelo GARCH trivariado asimétrico - Fátima Irina Villalba Padilla; Miguel Flores-Ortega (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2014)
– We jointly parameterized the generalized autoregressive conditional het- eroskedasticity that corresponds to the behavior of the variance of three variables: (a) the core Mexican stock market index (IPC), (b) the Emerging Markets Bond Index for Mexico (EMBI) as country risk pointer and, (c) the Mexican three oil basket exports mix (MEZCLA). The variables are used as trend indicators of stocks, bonds and energetics respectively with the ultimate goal of forming a diversified portfolio including such assets. This paper presents the empirical results of an asymmetric econometric trivari- ate GARCH model. The model incorporates the covariance between the variables in order to explain their relationship and we considered the shocks generated by positive and negative innovations. The study involves the pe- riod 2002 - 2013.
Keywords: C22; C52; C58; 330; volatilidad; rendimiento; asimetría; GARCH trivariado; pronóstico